Association of Sheep Tail Type with the T Gene Single Nucleotide Polymorphisms Loci - Daqing Wang; Yifan Zhao; Wenjing Fang; Junxi Liang; Kuo Li; Caiyun Wang; Guifang Cao (Life)
This study aimed to develop an effective tail typing detection technology based on the TaqMan probe technology for genotyping different sheep tail types. A total of 122 Hulun Buir short-tailed sheep and 50 Hu sheep were enrolled in the study to compare their tail morphologies, lengths, and widths. Through the Sanger sequencing of loci 333 and 334 in the second exon of the T gene, distinct genotypes of various types of Hulun Buir short-tailed sheep and Hu sheep were identified. In addition, the TaqMan probe technology was employed to genotype the two SNP loci of the T gene in the two types of sheep. It was observed that the second exon of the T gene in Hulun Buir short-tailed sheep at loci 333 and 334 exhibited two genotypes, CT/CT and CT/GG, but this feature was not detected for the T gene in Hu sheep. The detection accuracy of the TaqMan probe technology for sheep tail types exceeded 70%, suggesting that it is an effective tail-typing detection technology. This study provides a solid economic foundation and theoretical ideas that will improve the breeding of short-tailed sheep.